Pengembangan LKPD Terintegrasi STEM-PjBL (Science, Technology, Engineering, and Mathematics-Project Based Learning) pada Materi Minyak Bumi - Indra Dwynda; Effendi Effendi (Edukimia, 2020)
Education 4.0 emphasizes 4C skills, critical thinking, creativity, communication and collaboration. Realized with STEM-PjBL integrated learning, one of them was in the Petroleum material grade XI of SMA or MA. This study aims to produce STEM-PjBL integrated LKPD in Petroleum material and determine its validity. This type of research is R and D with a 4-D model composed of define, design, develop, and disseminate (not implemented). Research is limited to the validity test with the instrument validity as a measurement tool. Data collection techniques through questionnaires and analysis of research data from five expert validators using the Cohen kappa formula. Based on the analysis concluded, LKPD has had very high validity.